2014
DOI: 10.1016/j.icarus.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Methane depletion in both polar regions of Uranus inferred from HST/STIS and Keck/NIRC2 observations

Abstract: From Space Telescope Imaging Spectrograph (STIS) observations of Uranus in 2012, when good views of its north polar regions were available, we found that the methane volume mixing ratio declined from about 4% at low latitudes to about 2% at 60• N and beyond. This depletion in the north polar region of Uranus in 2012 is similar in magnitude and depth to that found in the south polar regions in 2002. This similarity is remarkable because of the strikingly different appearance of clouds in the two polar regions: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
120
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(136 citation statements)
references
References 27 publications
15
120
1
Order By: Relevance
“…This supports the view (Yelle et al 1989;Moses 2008;Orton et al 2014b, and references therein) that vertical transport depends on latitude, with global circulation effectively decreasing the strength of atmospheric mixing in the stratosphere at high latitudes. This picture could be consistent with the decrease of the upper tropospheric methane from equator to pole (Karkoschka & Tomasko 2009;Sromovsky et al 2014), possibly caused by upward transport of CH 4 -rich air at low latitudes and downward motion of CH 4 -dessicated air over the poles, provided that these cells extend into the stratosphere. Time variability of the convective activity, being more developed near Equinox, is also possible and is supported by the surge of cloud activity near equinox -except at high southern latitudes (Sromovsky et al 2012).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This supports the view (Yelle et al 1989;Moses 2008;Orton et al 2014b, and references therein) that vertical transport depends on latitude, with global circulation effectively decreasing the strength of atmospheric mixing in the stratosphere at high latitudes. This picture could be consistent with the decrease of the upper tropospheric methane from equator to pole (Karkoschka & Tomasko 2009;Sromovsky et al 2014), possibly caused by upward transport of CH 4 -rich air at low latitudes and downward motion of CH 4 -dessicated air over the poles, provided that these cells extend into the stratosphere. Time variability of the convective activity, being more developed near Equinox, is also possible and is supported by the surge of cloud activity near equinox -except at high southern latitudes (Sromovsky et al 2012).…”
Section: Discussionsupporting
confidence: 71%
“…Despite nearly identical globally averaged tropopause temperatures, stratospheric CH 4 is strongly enhanced in Neptune vs. Uranus (Baines & Hammel 1994). Furthermore, both planets exhibit nonuniformly mixed, subsaturated, and latitudinally variable CH 4 profiles below the 1.5 bar level (Karkoschka & Tomasko 2011;Sromovsky et al 2014). These findings indicate that non-1D and presumably seasonally variable processes are at work, such as upwelling and downwelling convective cells…”
Section: Introductionmentioning
confidence: 94%
“…Lindal et al (1987) derived temperature and methane profiles for the outer atmosphere of Uranus consistent with radio occultation observations. These profiles, labeled A-F, are characterized by their deep methane mixing ratio which ranges from <2% for profile A to 4% for profile F. Sromovsky et al (2011Sromovsky et al ( , 2014) created additional methane profiles (D1, DE, E1, EF, F1, FG, and G) with associated temperature profiles, consistent with the same observations. The wavelength range we are analyzing is less suited to constraining the deep methane mixing ratio than previous observations; we therefore limit our models to three methane profiles (D1, E1, and F1 with deep volume mixing ratios of 2.22%, 3.20% and 4%) with associated temperature profiles.…”
Section: Particle Scattering Propertiessupporting
confidence: 67%
“…Recently, numerous authors have found that invoking a greater methane abundance over the equator than the poles is required to fit observations (Karkoschka and Tomasko, 2009;Sromovsky et al, 2011Sromovsky et al, , 2014Irwin et al, 2012a;Tice et al, 2013). Sromovsky et al (2011) found they were unable to fit both equatorial and polar spectra with the same vertical distribution of methane, and constructed depleted methane profiles with various depletion degrees and shapes to fit the polar data.…”
Section: Methane Depletionmentioning
confidence: 99%
“…The extreme 98 o obliquity of Uranus subjects the atmosphere to extremes of seasonal forcing, with each pole spending decades in darkness. Despite the bland visible appearance of Uranus from Voyager, recent ground-based observations (e.g., Sromovsky et al, 2007Sromovsky et al, , 2009Sromovsky et al, , 2014de Pater et al, 2011;Fry et al, 2012) have shown the planet to be more dynamically active than previously thought (Fig. 4).…”
Section: How Is Uranus' Atmospheric Structure and Composition Influenmentioning
confidence: 78%